Experts' cognitive task analysis in multimedia design - Rafiza Abdul Razak (Institute of Education, International Islamic University Malaysia, 2011)
The research identified and explored the cognitive knowledge among the instructional multimedia design and development experts comprising of multimedia designer, graphic designer, subject-matter expert and instructional designer. A critical need exists for a solid understanding of the factors that influence team decision making and performance in order to identify interventions that can affect the decision making process and improving performance. The knowledge shared by the team was categorized into three groups of multimedia design principles encompasses of basic principles, authoring principles and design principles. Even though a great deal of relevant research and theory exists, few have been implemented in the design of multimedia. Typically, guidelines for design of interactive multimedia systems have been based on intuitive beliefs of designers rather than being founded on relevant research and theory. Hence, this research explores the experts' cognitive knowledge in multimedia design and development. Furthermore, cognitive task analysis was used to capture accurate and complete descriptions of cognitive processes and decisions among the experts in multimedia design and development. The research methodology involved two types of methods; quantitative and qualitative. Sequentially, the research began with quantitative method and followed by the qualitative method. Initial phase began with the modified Delphi technique which involved a selection of experts and the list of principles in multimedia design. Next phase, the interview session involved four selected experts to verify the list of principles and obtain detailed information. Predominantly,, the research presented two major findings; the empirically-based multimedia design principles and shared knowledge among multimedia design experts. The research outcomes significantly benefit the Ministry of Education, teachers, students, instructors, designers and the field of instructional design instructional design. Consequently, quality multimedia learning products can be produced.